Improving Interactive Multimedia Based Learning Media for Elementary School Students - Erni Pradita; Zakiya Ramadhina Azhar; Wahyu Kurniawati (Sean Institute, 2024)
This study aims to develop interactive multimedia-based learning media for solar system material for grade VI elementary school students that is feasible in terms of validity, practicality, and effectiveness. The method used in research is research and development or Research and Development using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research data collection instruments were media expert validation sheets, material expert validation sheets, teacher questionnaire sheets, student questionnaire sheets, pretest and posttest. The data analysis technique used in this study is the validity test, the practicality test and the effectiveness test of learning media. The results of the learning media validity data were obtained based on the results of the media validation assessment by experts who obtained a percentage of 96.67% in the